Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1964
DOI: 10.1021/je60022a047
|View full text |Cite
|
Sign up to set email alerts
|

Viscosities of Binary Mixtures of Benzyl Acetate with Dioxane, Aniline, and m-Cresol.

Abstract: Accurate measurements of viscosity as a function of composition of binary mixtures of benzyl acetate with dioxane, aniline and mefo-cresol are reported. The data are interpreted in terms of Eyring's relation for the viscosity of pure liquids. The value of the interaction energy Wvisc is calculated for each of the three mixtures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
153
0
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(155 citation statements)
references
References 5 publications
1
153
0
1
Order By: Relevance
“…[1][2][3][4][5] Knowledge of density and viscosity is important in designing the processes involving chemical separations, equipment design, solution theory, heat transfer, fluid flow and molecular dynamics. The research findings [6][7][8][9][10] proved that the data on viscosity are useful for testing the theories and empirical relations of liquid mixtures. The study of the ultrasonic velocity in liquids and liquid mixtures and its influence on molecular structure were studied by several researchers.…”
Section: Introductionmentioning
confidence: 82%
“…[1][2][3][4][5] Knowledge of density and viscosity is important in designing the processes involving chemical separations, equipment design, solution theory, heat transfer, fluid flow and molecular dynamics. The research findings [6][7][8][9][10] proved that the data on viscosity are useful for testing the theories and empirical relations of liquid mixtures. The study of the ultrasonic velocity in liquids and liquid mixtures and its influence on molecular structure were studied by several researchers.…”
Section: Introductionmentioning
confidence: 82%
“…This study will also provide an attest of various interaction parameters. The viscosities were used to test the semiempirical relations of Grunberg and Nissan 3 Katti and Chaudhri 4 and Hind et al. 5 The suitability of these theories and relations for the present liquid mixtures was checked.…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier paper, we had studied the transport properties of binary liquid mixtures. 4,5 In continuation of this research, we have reported density (ρ), viscosity (η), refractive index (n D ) and ultrasonic velocity (u) of pure acetophenone and ethylchloroacetate as well as for the binary system constituted by these two chemicals at temperatures of 303.15, 313.15 and 323.15 K. The viscosity values have been fitted to Grunberg and Nissan, 6 Hind et al, 7 Tamura and Kurata, 8 Katti and Chaudhari, 9 Sedgwick, 10 McAllister…”
Section: Introductionmentioning
confidence: 99%